Developing Algorithms for the Internet of Flying Things Through Environments With Varying Degrees of Realism - Lamenza, Thiago; Kamysek, Josef; Souza, Bruno José Olivieri de; Endler, Markus (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2024: Anais Estendidos do XLII Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc_estendido.2024.2305, 2024)
Developing for the internet of flying things is a complicated task. The fragility and cost of the equipment required to deploy in the field motivates the use of simulation software for prototyping and developing robust applications. This work proposes GrADyS-SIM NextGen as a solution that enables development on a single programming language and toolset over multiple environments with varying levels of realism. Finally, we illustrate the usefulness of this approach with a toy problem that makes use of the simulation framework.